Bulimia symptoms and anger and aggression among adolescents - Roman Koposov; Andrew Stickley; Denis Sukhodolsky; Vladislav Ruchkin (BMC, 2023)
Abstract Background Previous research has indicated that anger and aggression may be elevated in adolescents with a bulimia nervosa (BN) diagnosis. However, as yet, little is known about whether bulimia symptoms are linked to anger and aggression in adolescents in the general population. To address this deficit this study aimed to explore the associations between a clinical level of bulimia symptoms (CLBS) and anger, anger rumination and aggression in community-based adolescents, and determine whether gender is important in this context. Methods This study was conducted on a representative sample of youth from northwestern Russia (n = 2613, age 13-17 years old, 59.5% female) using self-report scales. A proxy variable for a CLBS was created using the Eating Disorder Diagnostic Scale. Aggression, anger and anger rumination were assessed by the Trait Anger Scale of the State Trait Anger Expression Inventory, the Anger Rumination Scale, and scales created to assess physically and verbally aggressive behavior. Multivariate analysis of covariance was used to examine the associations between the study variables. Results A CLBS was more prevalent in girls than in boys (13.4% vs. 3.5%). The association with anger and aggression was stronger in both genders with a CLBS, compared to those adolescents without a CLBS. In the CLBS group, boys as compared to girls scored higher on verbal and physical aggression, anger rumination and social aggression. In both the CLBS and Non-CLBS groups higher anger and aggression scores were associated with increasing age. Conclusions Findings suggest that aggression and anger rumination are elevated in adolescents with BN symptoms, and that the associations between anger, aggression and BN symptoms may be stronger in boys. As previous research has indicated that the presence of aggressive behaviors may affect the prognosis of BN and complicate management of the disorder, clinician screening for these behaviors in adolescents with BN symptoms may facilitate the provision of more effective treatment, especially among boys.